STRESS AND IMMUNITY: BRIEF REVIEW OF MECHANISMS IN PSYCHONEUROIMMUNOLOGY - Mohan, Aparajitha (Innoriginal: International Journal of Sciences, 2018)
Psychoneuroimmunology is the term used for the interaction of the psychological stimulus with the immune system. The main objective of this paper is to have a thorough review of the mechanisms behind the immune changes during stress. This review includes various studies and methodologies forming a basis in understanding how a stressed individual would have immune suppression with increased susceptibility to various diseases. Understanding of these concepts over the years has now resulted in treatment modalities like immune checkpoint therapy for various illnesses like cancer and how they are modulated by the psychic stimuli. This study emphasises on the need for providing support and creating a positive environment around diseased individuals to enhance their immunity and have a great relief from any knid of stress. KEYWORDS: Immunity, Psychoneuroimmunology, Stress.